KESESUAIAN PEMETAAN PENGGUNAAN LAHAN PEMUKIMAN DENGAN KONDISI SEBENARNYA DI KECAMATAN KATOBU DAN KECAMATAN DURUKA KABUPATEN MUNA - Andri Estining Sejati; Muhammad Hasan; La Ode Nursalam; Eko Harianto; Deris Deris (Tunas Geografi, 2020)
The population in Katobu District and Duruka District are always increased. BPS data shown increased from 2011 to 2018 in Katobu District as much 3.194 people and Duruka District as much as 1.205 people. This caused the requirement of settlement area also increased. The research aim was to determine the suitability between settlement land use map and actual conditions in Katobu District and Duruka District. This research type is a regional survey. Data were collected by interviews and observations. Data were analyzed using quantitative descriptive with percentage and scoring. The results shown the settlements map in Katobu and Duruka Districts in the S1 category 53.65%, S2 4.46%, and N1 41.89%. The suitability between settlement map in Katobu and Duruka Districts with actual conditions reached 100%. This showed that the GIS spatial analysis map results can be used in determining policies or public consumption related to the suitability of settlement locations in Katobu District and Duruka District of Muna Regency.Keywords: suitability, actual conditions, settlement mapping Jumlah penduduk di Kecamatan Katobu dan Kecamatan Duruka selalu meningkat. Data BPS menunjukkan peningkatan dari tahun 2011 ke 2018 di Kecamatan Katobu sebanyak 3.194 jiwa dan kecamatan Duruka sebanyak 1.205 jiwa. Hal ini menyebabkan kebutuhan akan lahan permukiman juga meningkat. Tujuan penelitian ini untuk mengetahui kesesuaian peta penggunaan lahan permukiman dengan kondisi sebenarnya di Kecamatan Katobu dan Kecamatan Duruka. Jenis penelitian ini adalah survey wilayah. Cara pengumpulan data dengan wawancara dan observasi. Data dianalisis menggunakan deskriptif kuantitatif dengan persentase dan skoring. Hasil menunjukkan peta permukiman di Kecamatan Katobu dan Kecamatan Duruka pada kategori S1 53,65%, S2 4,46%, dan N1 41,89%. Kesesuaian peta permukiman di Kecamatan Katobu dan Kecamatan Duruka dengan kondisi sebenarnya mencapai 100%. Hal ini menunjukkan bahwa peta hasil analisis spasial SIG dapat digunakan dalam penentuan kebijakan atau konsumsi masyarakat terkait kesesuaian lokasi permukiman di Kecamatan Katobu dan Kecamatan duruka Kabupaten Muna.Kata Kunci: kesesuaian, kondisi sebenarnya, pemetaan permukiman